PERBANDINGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLANING DENGAN MODEL PEMBELAJARAN LANGSUNG PADA SISWA KELAS XI MIA MAN SUNGAI GELAM KABUPATEN MUARO JAMBI - relawati relawati; Risma Simamora (Universitas Batanghari Jambi, 2017)
This research is based on facts in the research location. Based on the results of preliminary observation in MAN Sungai Gelam Muaro Jambi Regency, the facts given in relation to the still poor problem solving problems mathematically students, seen from the answer given problem. In this study the population is all students of grade XI MIA MAN Sungai Gelam. The results showed that students' mathematical problem solving ability using Student Facilitator and Explaning learning model in teaching mathematics of the subject of relation and function in grade XI MIA MAN Sungai Gelam that is: (1) Based on the result of posttest obtained the result of learning mathematics of student of sample class on relation material and function for the experimental class using Student Facilitator And Explaining learning model obtained an average of 8.2 and control class using direct learning model obtained an average of 5.8 (2) Based on the final result it can be concluded that the problem solving ability of students using mathematical Student Facilitator And Explaning learning model is higher than direct learning model of XI MIA MAN Sungai Gelam Kabupaten Muaro Jambi.Keywords: Learning Model Student Facilitator And Explaning, Mathematical Problem Solving abilities